Penerapan Model Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (ICT-Based Learning) untuk Meningkatkan Motivasi Belajar Siswa: Implementing Information and Communication Technology-Based Learning (ICT-Based Learning) Models to Increase Student Learning Motivation - Wahyuli Lius Zen; Ilpi Zukdi; Zulfahmi Zulfahmi; Zulvia Trinova (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
The research aims to determine the use of ICT-based learning models on students’ learning motivation at Darul Falah High School. The object of the research was students of Class X of Darul Falah High School, namely to see whether students’ abilities in ICT-based learning in geography subjects increased students learning motivation. The research method used is the classroom action research method. The term classroom action research emphasizes class as a research setting. The research developed was in the form of a cyclical review process consisting of four stages, namely (1) planning, (2) implementation, (3) observation and (4) reflection. The results of this study are students’ learning motivation before participating in Information and Communication Technology (ICT)-based learning. There is no enthusiasm for learning. Students chatted more, did not focus on the lesson, and did not want to discuss and do assignments well. There is no competition to get good grades, and learning objectives have not been achieved. Understanding of the subject matter has not appeared. Implementing ICT-based learning provides benefits, including being more practical and making it easier for teachers to deliver subject matter. Students find it easier to access information related to the subject matter. This is supported by facilities and infrastructure in schools that support the ICT-based learning process, namely the existence of internet facilities.